Isolation and molecular characterization of bacterial species from Sikog waterfall, Padawan, Sarawak - Stanley, Sait; Samuel, Lihan; Flonia, Benet; Scholastica Ramih, Bunya; Khairunnisa, Mohammad Hamdi (Malaysian Society for Microbiology, 2023)
Aims: Bacteria are microorganisms that are commonly distributed in any environment. They are also found abundantly in marine environments such as waterfalls and rivers. Some bacteria participate in various biological activities and possess no health risk; however, other species could be pathogenic and have been directly associated with various diseases in animals and humans. Therefore, it is crucial to analyze the antibiotic resistance profiles of bacteria in the research area based on regularly used antibiotics in clinical and agricultural contexts to establish a data baseline for health providers and public usage. Methodology and results: Water samplings were done twice and collected from upstream, midstream, and downstream of the Sikog waterfall. A total of ninety isolates were isolated and analyzed using (GTG)5 genetic fingerprinting to determine the genetic similarities. Based on the dendrogram generated using Gelj Version 2.0 software, 41 bacterial isolates were subjected to 16S rRNA gene sequencing for species identification. The Kirby-Bauer disk diffusion method was implemented to determine the level of susceptibility toward certain antibiotics. Sequence analysis was performed using BLAST, revealing that the isolates constitute 17 genera, including Pseudomonas, Alcaligenes, Stenotrophomonas, Staphylococcus, Bacillus, Lysinibacillus, Rossellomorea, Citrobacter, Enterobacter, Kosakonia, Klebsiella, Escherichia, Serratia, Cronobacter, Aeromonas, Chromobacterium and Kocuria. According to the overall antibiotic susceptibility analysis, streptomycin (10 µg) exhibited the highest rate of resistance among bacterial isolates, with 36.84%, followed by penicillin (10 units) (36.36%), rifampicin (5 µg) (27.27%) and ampicillin (10 µg) (26.32%). Conclusion, significance and impact of study: The research findings revealed the predominant bacteria found in the recreational water of Sikog waterfall and their antibiotic susceptibility, which could be helpful in the treatment of bacterial infections for future clinical reference. Simultaneously, the public, particularly communities in the study area, should be informed about the potential health risk associated with diverse resistant enteric bacteria in the recreational water.